Developmental and digestive flexibilities in the midgut of a polyphagous pest, the cotton bollworm, helicoverpa armigera - Sarate, P. J.; Tamhane, V. A.; Kotkar, H. M.; Ratnakaran, N.; Susan, N.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Insect Science, 2012)
Developmental patterns and survival of the cotton bollworm, Helicoverpa armigera Hubner (Lepidoptera: Noctuidae), a polyphagous insect pest, have been studied with reference to the effect of diet on major gut digestive enzymes (amylases, proteases, and lipases). Significant correlations between nutritional quality of the diet and larval and pupal mass were observed when H. armigera larvae were fed on various host plants viz. legumes (chickpea and pigeonpea), vegetables (tomato and okra), flowers (rose and marigold), and cereals (sorghum and maize). Larvae fed on diets rich in proteins and/or carbohydrates (pigeonpea, chickpea, maize, and sorghum) showed higher larval mass and developed more rapidly than larvae fed on diets with low protein and carbohydrate content (rose, marigold, okra, and tomato). Low calorific value diets like rose and marigold resulted in higher mortality (25-35%) of H. armigera. Even with highly varying development efficiency and larval/pupal survival rates, H. armigera populations feeding on different diets completed their life cycles. Digestive enzymes of H. armigera displayed variable expression levels and were found to be regulated on the basis of macromolecular composition of the diet. Post-ingestive adaptations operating at the gut level, in the form of controlled release of digestive enzymes, might be a key factor contributing to the physiological plasticity in H. armigera.
Keywords: amylases; larval performance; Lipases; Proteases

Differential protease activity augments polyphagy in helicoverpa armigera - Chikate, Yojana R.; Tamhane, V. A.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Insect Molecular Biology, 2013)
Helicoverpa armigera (Lepidoptera: Noctuidae) and other polyphagous agricultural pests are extending their plant host range and emerging as serious agents in restraining crop productivity. Dynamic regulation, coupled with a diversity of digestive and detoxifying enzymes, play a crucial role in the adaptation of polyphagous insects. To investigate the functional intricacy of serine proteases in the development and polyphagy of H.armigera, we profiled the expression of eight trypsin-like and four chymotrypsin-like phylogenetically diverse mRNAs from different life stages of H.armigera reared on nutritionally distinct host plants. These analyses revealed diet- and stage-specific protease expression patterns. The trypsins expressed showed structural variations, which might result in differential substrate specificity and interaction with inhibitors. Protease profiles in the presence of inhibitors and their mass spectrometric analyses revealed insight into their differential activity. These findings emphasize the differential expression of serine proteases and their consequences for digestive physiology in promoting polyphagy in H.armigera.
Keywords: adaptation; chymotrypsin; Helicoverpa armigera; polyphagy; Trypsin